Coulomb decay rates in monolayer doped graphene. Issue 4 (13th January 2020) - Chiu, Chih-Wei; Chung, Yue-Lin; Yang, Cheng-Hsueh; Liu, Chang-Ting; Lin, Chiun-Yan
Abstract : Excited conduction electrons, conduction holes, and valence holes in monolayer electron-doped graphene exhibit unusual Coulomb decay rates. Abstract : Excited conduction electrons, conduction holes, and valence holes in monolayer electron-doped graphene exhibit unusual Coulomb decay rates. The deexcitation processes are studied using the screened exchange energy. They might utilize the intraband and interband single-particle excitations, as well as the plasmon modes, depending on the quasiparticle states and the Fermi energies. The low-lying valence holes can decay through the undamped acoustic plasmon, so that they present very fast Coulomb deexcitations, nonmonotonous energy dependence, and anisotropic behavior. However, the low-energy conduction electrons and holes are similar to those in a two-dimensional electron gas. The higher-energy conduction states and the deeper-energy valence ones behave similarly in the available deexcitation channels and have a similar dependence of decay rate on the wave vector.